2013
DOI: 10.1093/jrr/rrt033
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical trial of tumor hypoxia imaging with 18F-fluoromisonidazole positron emission tomography and computed tomography (F-MISO PET/CT) before and during radiation therapy

Abstract: To visualize intratumoral hypoxic areas and their reoxygenation before and during fractionated radiation therapy (RT), 18F-fluoromisonidazole positron emission tomography and computed tomography (F-MISO PET/CT) were performed. A total of 10 patients, consisting of four with head and neck cancers, four with gastrointestinal cancers, one with lung cancer, and one with uterine cancer, were included. F-MISO PET/CT was performed twice, before RT and during fractionated RT of approximately 20 Gy/10 fractions, for ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Thus, for monitoring of treatment response, effects must induce a greater change than this to be detectable. Studies investigating dynamics of hypoxic areas before and during (chemo)radiation suggest that hypoxia indeed changes in the course of treatment and moreover, residual hypoxia after the first courses of treatment has a higher prognostic value than baseline hypoxia [26,[42][43][44][45][46]. The normal variation in [ 18 F]HX4 uptake we found in this study was lower than the changes found during treatment, suggesting it to be able to assess these changes and thus as a potential tool for early response evaluation.…”
Section: Discussionmentioning
confidence: 47%
“…Thus, for monitoring of treatment response, effects must induce a greater change than this to be detectable. Studies investigating dynamics of hypoxic areas before and during (chemo)radiation suggest that hypoxia indeed changes in the course of treatment and moreover, residual hypoxia after the first courses of treatment has a higher prognostic value than baseline hypoxia [26,[42][43][44][45][46]. The normal variation in [ 18 F]HX4 uptake we found in this study was lower than the changes found during treatment, suggesting it to be able to assess these changes and thus as a potential tool for early response evaluation.…”
Section: Discussionmentioning
confidence: 47%
“…Koh et al [221] , Liu et al [222] , Yeh et al [223] , Rischin et al [224] , Bentzen et al [125] , Rajendran et al [225] , Gagel et al [126] , Rajendran et al [226] , Hicks et al [227] , Lawrentschuk et al [200] , Loi et al [228] , Thorwarth et al [229] , Rajendran et al [230] , Rischin et al [231] , Thorwarth et al [232] , Zimny et al [124] , Eschmann et al [233] , Gagel et al [202] , Thorwarth et al [234] , Thorwarth et al [235] , Lee et al [236] , Lin et al [237] , Nehmeh et al [238] , Roels et al [239] , Dirix et al [240] , Lee et al [241] , Mortensen et al [127] , Wang et al [56] , Abolmaali et al [242] , Bowen et al [138] , Eary et al [243] , Kikuchi et al [244] , Hugonnet et al [131] , Yamane et al [245] , Mammar et al [246] , Zips et al [247] , Cheng et al [217] , Henriques de Figueiredo et al [248] , Okamoto et al [249] , Sato et al [218] , Segard et al [250] , Tachibana et al [251] , Norikane et al [219] [ Dubois et al …”
Section: F]fmisomentioning
confidence: 99%
“…Several studies using an animal model observed reoxygenation after fractionated radiation and the efficacy of dose escalation [15][16][17][18][19]. A number of other studies reported a reduction of FMISO uptake in hypoxic tumors during or after radiation therapy [20][21][22][23][24][25]. On the other hand, the tumoricidal effect during radiation also affects FMISO-PET results.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells that have been killed by irradiation no longer exhibit tumor hypoxia. However, the abovementioned reports [20][21][22][23][24][25] did not discuss the tumoricidal effect, and it is thus difficult to reach any conclusions regarding whether the reduction of FMISO uptake during radiotherapy is due to reoxygenation or to the tumoricidal effect. In order to confirm the occurrence of reoxygenation due to radiotherapy, comparisons of hypoxic changes and tumoricidal effects are necessary.…”
Section: Introductionmentioning
confidence: 99%